Citizenship Pressure as a Predictor of Daily Enactment of Autonomous and Controlled Organizational Citizenship Behavior: Differential Spillover Effects on the Home Domain - Germeys, Lynn; Griep, Yannick; De Gieter, Sara (Frontiers in Psychology, 2019)
This study questions the exclusive discretionary nature of organizational citizenship behavior (OCB) by differentiating between autonomous OCB (performed spontaneously) and controlled OCB (performed in response to a request from others). We examined whether citizenship pressure evokes the performance of autonomous and controlled OCB, and whether both OCB types have different effects on employees’ experience of work-home conflict and work-home enrichment at the within- and between-person level of analysis. A total of 87 employees completed two questionnaires per day during ten consecutive workdays (715 observations). The results of the multilevel path analyses revealed a positive relationship between citizenship pressure and controlled OCB. At the within-person level, engaging in autonomous OCB resulted in an increase of experienced work-home conflict and work-home enrichment. At the between-person level, enactment of autonomous OCB predicted an increase in experienced work-home enrichment, whereas engaging in controlled OCB resulted in increased work-home conflict. The divergent spillover effects of autonomous and controlled OCB on the home domain provide empirical support for the autonomous versus controlled OCB differentiation. The time-dependent results open up areas for future research.